Method for Calculating Locomotive Traction & Brake Limited Line Based on Binary Search and Lagrange Interpolation - HUANG Hao; CAO Xiao; HE Wei (机车电传动)
A method was proposed by using binary search arithmetic searching motor speed, if missed then employing Lagrange interpolation method to calculating motor torque of locomotive’s traction and brake. By comparing calculation accuracy and time complexity with the classical algorithm in envelope curve of motor characteristic, the presented method was proved have better calculation accuracy and acceptable time complexity.